Global Incidence of IgA Nephropathy by Race and Ethnicity: A Systematic Review - Kiryluk, Krzysztof; Freedberg, Daniel E.; Radhakrishnan, Jai; Segall, Leslie; Jacobson, Judith S.; Mathur, Mohit; Mohan, Sumit; Neugut, Alfred I. (Kidney360, 2023)
Key PointsIn 16 studies conducted abroad, IgA nephropathy incidence varied from 0.06 in South Africa to 4.2 per 100,000 in Japan.Globally, the incidence of IgA nephropathy seemed higher in Asians than in non-Asians and higher in male patients than in female patients.Five studies conducted in the United States found no consistent difference in incidence between Black patients and White patients.BackgroundThe reported incidence of IgA nephropathy varies widely across studies and may vary on the basis of race/ethnicity. This study systematically reviewed the incidence of IgA nephropathy in the United States and other countries and explored variability on the basis of the racial/ethnic composition and other demographic characteristics of different populations.MethodsThis was a systematic review. Studies were eligible for inclusion if they contained data collected from January 1, 1974, to December 31, 2021, and reported IgA nephropathy incidence at a population level (i.e., cases of IgA nephropathy per 100,000 population).ResultsFive US and 16 international studies were included; three of the US studies reported the race-specific incidence of IgA nephropathy. In the United States, the reported incidence of IgA nephropathy ranged from 0.39 per 100,000 in Tennessee to 1.4 per 100,000 in Minnesota; internationally, IgA nephropathy ranged from 0.06 per 100,000 in South Africa to 4.2 per 100,000 in Japan. Findings regarding the incidence of IgA nephropathy in the United States by race were inconsistent: One study found a higher incidence among White patients compared with Black patients, one study found a lower incidence in White patients, and one study found no difference. Globally, the incidence of IgA nephropathy seemed to be higher in Asian than in non-Asian populations and higher in male patients than in female patients.ConclusionsReported incidence of IgA nephropathy varies widely; there is no consensus regarding the relationship between race and IgA nephropathy. Incidence rates seemed to be higher in Asians than non-Asians and in male patients than female patients. We recommend that future studies should report IgA nephropathy incidence rates by race/ethnicity and account for the demographic characteristics of the background population.